FRI0155 Fifty Percent of Patients Who Tapered TNF-Blockers while in Stable Remission Are Able To Maintain A Tapered Regimen at 3 Year: Long Term Follow-Up Extension of The Strass Trial. (15th July 2016) - Sigaux, J.; Bailly, F.; Gossec, L.; Alfaiate, T.; Gandjbakhch, F.; Foltz, V.; Morel, J.; Dernis, E.; Gaudin, P.; Brocq, O.; Berthelot, J.-M.; Balblanc, J.-C.; et al.
Abstract : Background: Step-down strategy of spacing anti-tumor necrosis factor (TNF) agents in patients with rheumatoid arthritis (RA) in remission are feasible in the context of randomized clinical trials (RCTs). However, we lack information on the long-term sustainability of a DAS driven step down strategy in clinical practice. Objectives: This long-term extension study of a tapering RCT (STRASS trial (1)) aimed to assess the rate of patients who maintained the tapered regimen of etanercept (ETA) or adalimumab (ADA) in the in S-arm (progressive injection spacing) and M-arm (full regimen) and to evaluate the rate of treatment switch for inefficacy during the 3 years following the trial. Methods: This observational 36 months follow-up considered all patients who completed the STRASS RCT (1). During the follow-up, the physicians were completely free of therapeutic decision making. Physicians were contacted between April and October 2015 and the data on the 36-month period after the end of trial retrospectively collected. The co-primary outcomes were the rate of patients who were taking their initial biologic at tapered regimen and the switch rate for loss of efficacy or safety. Percentage of full regimen anti-TNF intake was calculated over the 3 first years after trial end in both arms, using data from 12-monthly follow-up time points. Results: 96 patients (70.1% of patients completing the RCT) had follow-up data available up to 3 years. At the end of the STRASS RCT (Table ), 72 (75%) were in LDA or remission: 47 (48.9%) were taking ETA, 35 (36.5%), ADA, 2 (2.1%) another biologic and 12 (12.5%) no biologic because of remission. In addition, amongst patients still on their initial TNF blockers, 59/80 (74%) were treated at full regimen, 21/80 (26%) at tapered regimen. 3 years later, 65/96 (67.7%) were still on their initial anti-TNF: 73.1% vs 61.4% respectively in M and S-arm, p=0.23), either at full regimen 36/96 (38%), tapered regimen 29/96 (30%, 32% vs 29%, p=0.75), or completely stopped (11.5%: 5.8% vs 18.2%, p=0.06). 28 patients (29.2%, 25% vs 34.1%, p=0.33) had switched for another biologic. The mean percentage of full regimen of antiTNF over 3 years was 70.1±30.4%: respectively 74.3±28.2% vs 64.6±32.9% (p=0.19). DAS28-VS was not different between M and S-arm (2.42 vs 2.01 (p=0.23)). Conclusions: Maintenance of anti-TNF was high (68% at 3 years) in this cohort of patients with established RA treated according to the treat-to-target paradigm, with no difference between the 2 initial RCT arms. More than 1/3 of patients were received tapered anti-TNF regimen. References: Fautrel B, ARD 2016;75(1):59–67 Disclosure of Interest: None declared